A comparative thermodynamic analysis of helium distribution systems with central and distributed precooling heat exchangers. (April 2019) - Fydrych, J; Pietrowicz, S
Abstract: All the cryogenic systems of large scientific facilities using He II technologies apply the Joule-Thomson expansion for final production of superfluid helium. Their cryogenic plants supply subcooled liquid helium at 4.5 K which is precooled to 2.2 K before throttling to a sub-atmospheric pressure in Joule-Thomson valves. The precooling of the 4.5 K helium can be done in one central heat exchanger or in a number of small heat exchangers located just at the throttling valves. Since there are cons and pros for the both architectures, it is important to take into account all thermodynamics and financial aspects in choosing the best layout in the preliminary design of any new large He II system. The paper presents a comparative thermodynamic analysis of the both cooling schemes in respect to the size of cryogenic distribution systems and heat loads subjected to their components. The analysis is based on calculations of the second-law efficiencies which are preceded by a numerical modelling of temperature and pressure distributions along the process lines.